Deteksi Perubahan Citra Pada Video Menggunakan Illumination Invariant Change Detection - Adri Priadana; Agus Harjoko (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2017)
There is still a lot of juvenile delinquency in the middle of the community, especially people in urban areas, in the modern era. Juvenile delinquency may be fights, wild racing, gambling, and graffiti on the walls without permission. Vandalized wall is usually done on walls of office buildings and on public or private property. Results from vandalized walls can be seen from the image of the change between the initial image with the image after a motion.This study develops a image change detection system in video to detect the action of graffiti on the wall via a Closed-Circuit Television camera (CCTV) which is done by simulation using the webcam camera. Motion detection process with Accumulative Differences Images (ADI) method and image change detection process with Illumination Invariant Change Detection method coupled with image cropping method which carried out a comparison between the a reference image or image before any movement with the image after there is movement.Detection system testing one by different times variations, ie in the morning, noon, afternoon, and evening. The proposed method for image change detection in video give results with an accuracy rate of 92.86%.